Evaluation of pendimethalin binding to human serum albumin: Insights from spectroscopic and molecular modeling approaches / Lee Wei Qi - Lee , Wei Qi (2017)

(untitled)
Interaction of pendimethalin (PM) herbicide with human serum albumin (HSA) was studied using fluorescence, circular dichroism (CD) and molecular modeling methods. The attenuation of the fluorescence intensity of HSA in the presence of PM revealed formation of the PM-HSA complex. Analysis of the fluorescence quenching data showed moderately strong binding affinity between PM and HSA. Both hydrophobic interactions and hydrogen bonds were suggested to stabilize the PM-HSA complex, based on thermodynamic data. Binding of PM to HSA induced perturbation in the microenvironment around the aromatic fluorophores as well as secondary and tertiary structural changes in the protein. Complex formation between PM and HSA led to an increase in its thermal stability. Both site marker displacement and molecular modeling results suggested site I, located in subdomain IIA, as the preferred binding site of PM on HSA. A comparative study on the interaction between PM and serum albumins of bovine (BSA), sheep (SSA), porcine (PSA), human (HSA) and rabbit (RbSA) was also made using fluorescence quenching titration and site marker displacement experiments. Similar magnitude of PM-induced fluorescence quenching was observed with BSA and HSA, compared to other albumins. The binding affinity of PM to these albumins was found to follow the order: SSA > HSA > BSA > RbSA > PSA. Warfarin (WFN) displacement results also suggested similar displacing action of PM on WFN-BSA and WFN-HSA complexes. All these results suggested close similarity between BSA and HSA in terms of PM binding characteristics.